Penguatan Tradisi Keislaman di Ma'had Putri Nurul Hasan MAN 2 Probolinggo : Implementasi Pengajian Kitab, Amalan Harian, dan Ritual Kolektif dalam Pembentukan Karakter Santri - Nurul Harifah; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines efforts to strengthen Islamic traditions at Ma'had Putri Nurul Hasan MAN 2 Probolinggo as an important part of building the character of religious, disciplined, and noble students. The Islamic traditions implemented include various routine activities such as studying the yellow book, dhikr together, reading the maulid, praying in congregation, and other daily practices. These activities are designed not only to strengthen students' understanding of Islamic teachings but also to create a spiritual environment that supports character formation based on Islamic values. With a qualitative-descriptive approach, this study describes in depth the implementation of Islamic traditions, the challenges faced, and their impact on the formation of students' characters. The results of the study show that strengthening Islamic traditions at Ma'had Putri Nurul Hasan not only succeeded in forming the religious character of students but also had a positive influence on their social and emotional lives. Traditions such as studying the yellow book using the bandongan and sorogan methods, as well as the integration of Islamic-based activities in the education curriculum, have been proven to be able to improve the discipline, responsibility, and social awareness of students. On the other hand, this study also found significant challenges in the implementation of Islamic traditions, including the influence of modernization and globalization that bring popular cultural values ​​that are less in line with Islamic teachings, limited infrastructure, and lack of family involvement in supporting Islamic education. This study concluded that despite facing various challenges, Islamic traditions at Ma'had Putri Nurul Hasan can remain relevant by adopting an innovative and collaborative approach. The use of digital technology, increasing teacher capacity, and strengthening synergy with families and the community are strategic steps that can support the sustainability of this program. This study not only contributes to the development of Islamic education in Indonesia but also becomes a model for other Islamic educational institutions in maintaining Islamic traditions as the identity and strength of the people in the modern